Biblical Theology of prayer in the Old Testament - Coetsee, Albert J. (Reformed Theology in Africa Series, 2023)
Prayer is a major topic within Christian theology. The biblical text has various references to various recorded and reported prayers. In fact, references to prayer are found within the rich diversity of the various books, corpora and genres of Scripture. As can be expected, much has been written about prayer in the biblical text. However, a comprehensive Biblical Theology dealing with the concept of prayer in Scripture has not been published before, and this book intends to fill this gap, assuming that such an approach can provide a valuable contribution to the theological discourse on prayer and related concepts. This book aims to investigate prayer and its related elements – including worship, praise, thanksgiving, adoration, petition, intercession, lament and confession – in the Old Testament on a book-by-book or corpus-by-corpus basis. The investigation follows a Biblical Theological approach, reading the Old Testament on a book-by-book basis in its final form to uncover the Old Testament’s overarching theology of prayer, understanding the parts in relation to the whole. By doing this, the discrete nuances of the prayers of the different Old Testament books and corpora can be uncovered, letting the books and corpora speak for themselves. In addition, the advantage of this approach is that it provides findings that can benefit the modern Christian community and contribute to the practice of Reformed theology in Africa. This book is of significant value to scholars. It will inspire scholars to think about prayer and use the Bible as the major ‘prayer handbook’ in their spiritual lives.